Religious Cultural Approach Group Counseling - ANDRA MAIROZA; Silvianetri Silvianetri (Jurnal Neo Konseling, 2023)
This study explores the importance of religion-based group counseling for individuals in different age groups in Indonesia as they progress through various stages of religious development. Religion significantly influences social and cultural diversity, and religious practices are integral to Indonesia's cultural heritage. Religion-based counseling prioritizes individuals with a religious background, utilizing their faith's values, norms, and teachings as a foundational framework. With the majority of Indonesians being Muslims, the Islamic counseling approach holds a strategic position. Religion-based group counseling serves as a viable solution to support individuals of all ages in their religious growth. Conducted as a literature review, this research collects and analyzes data from diverse sources to elucidate the significance of religion-based group counseling. The study contributes to a deeper understanding and practical application of religion-based group counseling in Indonesia, raising awareness of its necessity and benefits in facilitating optimal religious development across different stages of life.